An Analysis of the Long-Term Sustainability of the Large Companies Included in the Original Standard and Poor’s 500 Index - Jorge Moya; Marta Torres; Manuel Uche-Soria (Discrete Dynamics in Nature and Society)
The changes generated by the natural economic and social development have configured a scenario where the companies’ survival is gradually decreasing. This process is also impacting on the big corporations that were strongly consolidated for many years. This research has analysed that which of these major companies of the Fortune 500 Index have adapted themselves over the years and have survived. After locating the surviving companies, this paper studied the presence of elements of business quality in each of these firms. Then, using a fuzzy set methodology, this study obtained results that identified some of the main elements that might be considered as inductors of the business durability in the case of the big corporations: the effectiveness of the companies, the coherence with the mission, and the capacity of organisation are essential for the long-term sustainability of the companies especially if they are associated with a formalised structure of governance. The results also conclude that the simple presence of these elements is not enough for the permanence of the companies and only the progresses and improvements in these variables can guarantee the sustainability of the companies.